Identitas Kultural dan Gerakan Politik Kerapatan Adat Kurai dalam Representasi Politik Lokal - Irawati Irawati (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2012)
The strength of ethnic identity became public phenomena later gained momentum in West Sumatera when Nagari introducied be formal goverment. The Bukittinggi City Indigenous groups power incorporated in Kerapatan Adat Kurai (KAK) are not satisfied with the condition that Nagari are not applied in the City Government. KAK claims as a holder of authority over the area of Bukittinggi city is a source of strength to impose their demands. However during the reign of the new order, KAK losing their existence and influence over local politics. Losing their influence on formal governance, make KAK indigenous leaders trying to restore the system of Nagari Government which will give a space for them to power. There are indications that KAK demand is an attempt to restore the power of traditional elites. KAK movement more motivated by political interests to gain access and representation of their group within local government. The movement dynamics is closely linked with the interests of the actors to find support in a particular political event. The indigenous elite (traditional leaders) as the initiators have not obtained a good representation as politically, culturally and economically in local politics.